2021
DOI: 10.1002/pssb.202100068
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Investigation of the Stability, Electronic, Optical, and Thermoelectric Properties of BaLiP

Abstract: The density functional theory and post density functional theory techniques are used to investigate the properties of BaLiP for potential applications in photovoltaic and thermoelectric (TE) applications. Density functional calculations of the cohesive energy, phonon‐dispersion, and elastic constant studies establish structural, dynamical, and mechanical stability of the compound. Density functional calculations show that BaLiP is a direct bandgap semiconductor while optical properties at the Bethe–Salpeter eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, subsequent single‐crystal X‐ray diffraction studies on SrLiP and BaLiP revealed that these compounds crystallize in the related ZrBeSi type, listed above [24] . Available high‐throughput investigations within the density functional theory framework confirm higher stability of the ZrBeSi‐type structure in comparison to the SrPtSb‐type modification for SrLiP and BaLiP and suggest that the ZrBeSi type is more energetically favorable for BaLiAs as well [25,26] . Thus, it is quite probable that the SrPtSb type is in fact not adopted by any experimentally reported AEAPn compound.…”
Section: Resultsmentioning
confidence: 99%
“…However, subsequent single‐crystal X‐ray diffraction studies on SrLiP and BaLiP revealed that these compounds crystallize in the related ZrBeSi type, listed above [24] . Available high‐throughput investigations within the density functional theory framework confirm higher stability of the ZrBeSi‐type structure in comparison to the SrPtSb‐type modification for SrLiP and BaLiP and suggest that the ZrBeSi type is more energetically favorable for BaLiAs as well [25,26] . Thus, it is quite probable that the SrPtSb type is in fact not adopted by any experimentally reported AEAPn compound.…”
Section: Resultsmentioning
confidence: 99%